Quiet! There's a Canary in the Library - Freeman, Don 1908-1978. (New York : Viking, 2007)
Cary imagines a special day at the library when she invites only animals and birds to browse.
Originally published: San Carlos, Calif. : Golden Gate Junior Books, 1969.
Keywords: Libraries -- Fiction; Animals -- Fiction; Animal behavior -- Fiction; Human behavior -- Fiction